Coeliac disease with severe hypogammaglobulinaemia. Issue 2 (February 1981) - Webster, A D; Slavin, G; Shiner, M; Platts-Mills, T A; Asherson, G L
Abstract : A patient with severe late onset primary hypogammaglobulinaemia developed coeliac disease. The case illustrates that coeliac disease can occur in the virtual absence of local antibody production by plasma cells in the mucosa of the small bowel. Furthermore, our inability to demonstrate specific cellular immunity to a subfraction of gluten raises doubts about the relevance of immunological reactions in the pathogenesis of coeliac disease.